Metabolic reprogramming of fetal hematopoietic stem and progenitor cells by maternal obesity - Varlamov, Oleg (Frontiers in Hematology, 2025)
Maternal obesity, often linked to the consumption of a high-fat Western-style diet (WSD), poses significant risks to both maternal and fetal health. This review explores the impact of maternal obesity on fetal hematopoietic stem and progenitor cells (HSPCs), highlighting how metabolic and inflammatory shifts in the maternal environment affect HSPC proliferation, differentiation, and long-term immune system development. Maternal obesity leads to hormonal imbalances, increased inflammatory cytokines, placental insufficiency, and altered nutrient availability that disrupt normal HSPC function, potentially predisposing offspring to immune dysfunction, metabolic disorders, and cardiovascular diseases later in life. Notably, maternal obesity skews HSPC differentiation toward the myeloid lineage, which can impair adaptive immune responses and increase the risk of autoimmune diseases and infections. Furthermore, maternal diet-driven epigenetic and transcriptional reprogramming of fetal HSPCs exacerbates chronic inflammation, reinforcing a pro-inflammatory phenotype in downstream progeny that persists into postnatal stages. The review also emphasizes the need for further research to clarify the mechanisms underlying these effects across different species and developmental stages, as well as the potential for targeted interventions to mitigate the adverse impacts of maternal obesity on fetal hematopoiesis and lifelong health outcomes.